Diversifikasi Pengolahan Ikan Patin ( Pangasius pangasius) Menjadi Nugget Dengan Konsep Zero Waste Sebagai Upaya Pemenuhan Gizi Anak. - Desy Sasri Untari; Tri Adi Wibowo; Rohmatul Anwar; Titin Liana Febriyanti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Food is one of the sources of nutrition that greatly affects the growth of children. One of the food sources that contain food that contains nutrients in the form of protein and other minerals, namely fish, in this PkM uses one of the freshwater fish, namely Catfish (Pangasius pangasius) which has a fairly high protein content and contains all essential amino acids which contain higher lysine and arginine compared to milk protein and meat. In pkm activities carried out using the concept of Zero Waste, namely the use of the main raw material, namely catfish, with the use of all parts of the fish including bones to minimize waste in making nuggets. The purpose of this PkM is to provide knowledge and insight. PkM activities use socialization and question and answer methods by participants and speakers. The results of the socialization that has been carried out can add insight and knowledge to participants in an effort to fulfill child nutrition through diversification of the processing of catfish into nuggets with the concept of Zero Waste.